2003
DOI: 10.1016/s0002-9440(10)63838-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Furin Activity Enhances the Malignant Phenotype of Human Head and Neck Cancer Cells

Abstract: Many proteins are synthesized as inactive proforms requiring a proteolytic processing to render them active. A variety of proteases catalyze these cleavage reactions. Proprotein convertases are a family of serine proteases capable of activating substrates that will subsequently intervene in extracellular matrix (ECM) degradation, cell growth, differentiation and viral pathogenesis. Furin, the prototype of this family, has been implicated in many physiological and pathological processes. Some of its substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 35 publications
(39 reference statements)
1
82
0
Order By: Relevance
“…The reduced size of subcutaneous tumors in response to ␣1-PDX expression is likely due to differences in cell proliferation, as already reported in in vitro studies. [22][23][24] By histological staining with an antibody against Ki67, a nuclear protein expressed in proliferating cells, we confirmed that in situ cell proliferation was higher in PDX0-than in PDX39P-induced tumors (data not shown).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The reduced size of subcutaneous tumors in response to ␣1-PDX expression is likely due to differences in cell proliferation, as already reported in in vitro studies. [22][23][24] By histological staining with an antibody against Ki67, a nuclear protein expressed in proliferating cells, we confirmed that in situ cell proliferation was higher in PDX0-than in PDX39P-induced tumors (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…We, and others, previously observed that PCs inhibition leads to delayed tumor development and reduced tumor volume in nude or immunodeficient mice. [22][23][24][25] However, herein we used immunosuppressed newborn rats to test the metastatic dissemination. Results obtained with this animal model show that the role of PCs in tumor development and progression is far from being as simple as suggested by previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,[76][77][78] Increased activity of the MT1-MMP activator, furin, is associated with more aggressive in vitro and in vivo tumor activity in HNSCC. 79,80 In vitro and in vivo data similarly suggest that overexpression of MT1-MMP promotes HNSCC tumor cell invasion. 25,81 MT1-MMP plays a critical role in tumor cell invasion and angiogenesis through several known mechanisms: (1) activation of MMP-2, 77,82 (2) cleavage of the cell adhesion molecule CD44 from the cell surface, 83,84 (3) degradation of type I collagen and fibrin substrates, 29,85,86 and (4) enabling cell survival in three-dimensional matrices.…”
Section: Mt1-mmp As a Target For Selective Inhibition In Head And Necmentioning
confidence: 97%